Science and Technology for Humanity: An STS View from Singapore. Issue 1 (2nd January 2021) - Jasanoff, Sheila; McGonigle, Ian; Stevens, Hallam
Abstract: With this short essay, we aim to raise awareness of the NTU Institute of Science and Technology for Humanity (NISTH) initiative and to invite our colleagues to partake in the research programs we hope to see initiated at NISTH in years to come. In particular, building on the launch of the Institute, supplemented by the extraordinary global experience of COVID-19, we suggest ways in which STS scholars from around the world might contribute to the public conversation regarding the 4IR and thereby also to the ways in which the relationships between technology, states, and citizens might be imagined with specific reference to Asia's future.